2017
DOI: 10.1038/s41598-017-08835-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species–mediated switching expression of MMP-3 in stromal fibroblasts and cancer cells during prostate cancer progression

Abstract: Studies on the aberrant control of extracellular matrices (ECMs) have mainly focused on the role of malignant cells but less on that of stromal fibroblasts during cancer development. Herein, by using paired normal and prostate cancer-associated stromal fibroblasts (CAFs) derived from a coculture cell model and clinical patient samples, we demonstrated that although CAFs promoted prostate cancer growth, matrix metalloproteinase-3 (MMP-3) was lower in CAFs but elevated in prostate cancer cells relative to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Moreover, it has been shown that cancer exosomes could trigger MSC differentiation into pro-angiogenic and pro-invasive myofibroblasts, secreting high levels of matrix-regulating factors (MMP-1, -3, and -13), VEGF-A, and HGF [49]. A recent study reported MMP3 to be up-regulated in both stromal fibroblasts and cancer cells by oxidative stress [50]. Moreover, CCN2/CTGF can be produced from both tumor and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that cancer exosomes could trigger MSC differentiation into pro-angiogenic and pro-invasive myofibroblasts, secreting high levels of matrix-regulating factors (MMP-1, -3, and -13), VEGF-A, and HGF [49]. A recent study reported MMP3 to be up-regulated in both stromal fibroblasts and cancer cells by oxidative stress [50]. Moreover, CCN2/CTGF can be produced from both tumor and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cancer exosomes triggered MSC differentiation into pro-angiogenic and pro-invasive myofibroblasts secreting high levels of matrix regulating factors (MMP-1, -3 and -13), VEGF-A, and HGF [43]. A recent study reported MMP3 to be up-regulated in both stromal fibroblasts and cancer cells by oxidative stress [44].…”
Section: Clinical Significance Of Mmp3 Expressionmentioning
confidence: 99%
“…Tumor cells are surrounded by tumor stroma composed of various types of cells including cancer-associated fibroblasts (CAFs) with properties of mesenchymal stem cells (MSCs), tumorassociated immune cells including tumor-associated macrophages (TAMs), T cells, B cells, and dendritic cells (DCs), tumor endothelial cells (TECs), adipocytes, and normal epithelial cells. These stromal cells communicate with each other using cytokines, growth factors, MMPs [53], ECM, microRNAs, and EVs [54,55]. Earlier studies suggested that tumor stroma was tumor-suppressing, although recent studies have unveiled that stroma signals often drive tumor progression.…”
Section: Stromal Signal-driven Tumor Progressionmentioning
confidence: 99%
“…CAFs control ECM deposition and remodeling by producing fibronectin, collagen 1A1, tenascin C, osteopontin, and MMPs [62]. It has been shown that these secretory phenotypes of CAFs were often carried by EVs, including TGFβ, MMPs, microRNA, and ECMs, which alter epithelial cells, tumor cells, and tumor milieu [53,55,[62][63][64]. Proteomics of stroma-derived EVs is important to elucidate the mechanism of tumor progression.…”
Section: Stromal Signal-driven Tumor Progressionmentioning
confidence: 99%